If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -4 = 2 + 6s Reorder the terms: -4 + 3s = 2 + 6s Solving -4 + 3s = 2 + 6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6s' to each side of the equation. -4 + 3s + -6s = 2 + 6s + -6s Combine like terms: 3s + -6s = -3s -4 + -3s = 2 + 6s + -6s Combine like terms: 6s + -6s = 0 -4 + -3s = 2 + 0 -4 + -3s = 2 Add '4' to each side of the equation. -4 + 4 + -3s = 2 + 4 Combine like terms: -4 + 4 = 0 0 + -3s = 2 + 4 -3s = 2 + 4 Combine like terms: 2 + 4 = 6 -3s = 6 Divide each side by '-3'. s = -2 Simplifying s = -2
| -3.2=1+(-0.2) | | x=243 | | 7y-3=3 | | 12(5c-1)-4=58c+12 | | 14x-6x=56 | | 24+10x-x^2=0 | | 14x-6x=54 | | 12x-6x=54 | | 9z-5z=6 | | 5x+1-3x-64x+16=16x-1 | | -3y-8=6y+10 | | (4x^2)=36 | | 4(7x-2)=29x | | -5c+3=-2 | | (5x+20)=360 | | 4(4c-1)-5=13c+3 | | 5x+(20)=360 | | -39+6y+3=3(4y-2)-6 | | 33+4y-14=14y-9-3y | | -30y+95-35+2y=-24 | | -x+5x+6=8x+36 | | 6p^2+2p+3=0 | | 6p^2+2p-3=0 | | 4(x+2)=14-2(3-2x) | | 19.55=44.3-2.5x | | 15x-8x+7=42 | | -60.37=13.1-9.3x | | 4(c-3)+8=6+c-10 | | 0.2(22)+x=0.3(22+x) | | -16+2k=k-3k | | -45.9=9.9-6x | | 209.25=13.5+13.5x |